THE EXISTENCE AND DURABILITY OF PESANTREN DURING THE COVID-19 PANDEMIC - Moh Ashif Fuadi (IAIN Kendari, 2022)
The Covid-19 pandemic affects all elements of life. The impact is very felt not only on the economy and health but also has an impact on activities in pesantren. Islamic Boarding school becomes a crater candradimuka to educate students who learn religious science through the education of kiai. The five basic elements of pesantren, namely kiai, santri, dormitory, mosque, and yellow book, become a tree that should not be left behind. This research informs us about the existence of pesantren in efforts to mitigate the Covid-19 pandemic as well as its durability for the continuity of activities in pesantren by collecting previous research, relevant research libraries, news, or information related to handling pandemics in pesantren through online media. Then with the approach of structural functionalism, Talcott Parsons AGIL (adaptation, goal attainment, integration, latency) where social stem everywhere including pesantren is always related to interrelated elements so that pesantren will have endurance in carrying out its functions. The result of this research is that pandemics greatly impact the activities of pesantren typical with calves and culture. Various mitigations have also been done to prevent pesantren clusters, and through the AGIL approach, pesantren will be more responsive in dealing with the Covid-19 pandemic.